Translation of humor in the dubbed version of the sitcom “How I met your mother” in Vietnamese = Cách dịch yếu tố hài hước trong bản lồng tiếng phim hài tình huống “Khi bố gặp mẹ" - Nguyễn, Thị Hòa (2020)
Translation of humor in general and in audiovisual contexts in particular is challenging to even experienced translators, yet it has not attracted enough attention in the research field. In addition, translation of audiovisual products have unique characteristics requiring the collaboration between the audio and visual channel and undergoing a complicated editing process before being aired. This paper aims at discovering the translation of humor in a well-known sitcom named “How I met your mother” which has been dubbed by Vietnam Television network and the audience’s reception of that translation to enrich the materials in the field of screen humor translation. In order to collect the data on the types of humor available in the sitcom and the strategies used to translate the humor, the researcher used the method of observation of documents. Regarding audience’s reception, 80 students were asked to complete the questionnaire in which they showed their reaction to humorous excerpts from the dubbed version. After that, data was processed using numerical analyzation. The results presented that among eleven types of humor present in the chosen episodes of the sitcoms, irony, wordplay and teasing were the primary source of humor. Meanwhile, literal translation and explicitation were the dominating strategies used by the translators to render almost every type of humor present in the corpus. The reaction of 80 participants from FELTE, ULIS towards excerpts showed that most of them had a preference for literal translation over explicitation although students who watched sitcoms frequently had a more positive opinion towards explicitation than those who rarely did.